Immunization routes in cattle impact the levels and neutralizing capacity of antibodies induced against S. aureus immune evasion proteins. (December 2015) - Boerhout, Eveline; Vrieling, Manouk; Benedictus, Lindert; Daemen, Ineke; Ravesloot, Lars; Rutten, Victor; Nuijten, Piet; van Strijp, Jos; Koets, Ad; Eisenberg, Susanne
Abstract Vaccines againstS. aureus bovine mastitis are scarce and show limited protection only. All currently available vaccines are applied via the parenteral (usually intramuscular) route. It is unknown, however, whether this route is the most suitable to specifically increase intramammary immunity to combatS. aureus at the site of infection. Hence, in the present study, immunization via mucosal (intranasal; IN), intramuscular (triangle of the neck; IM), intramammary (IMM) and subcutaneous (suspensory ligament; SC) routes were analyzed for their effects on the quantity of the antibody responses in serum and milk as well as the neutralizing capacity of the antibodies within serum. The experimental vaccine comprised the recombinantS. aureus immune evasion proteins extracellular fibrinogen-binding protein (Efb) and the leukotoxin subunit LukM in an oil-in-water adjuvant combined with a hydrogel and alginate. The highest titer increases for both Efb and LukM specific IgG1 and IgG2 antibody levels in serum and milk were observed following SC/SC immunizations. Furthermore, the harmful effects of Efb and leukotoxin LukMF' on host-defense were neutralized by serum antibodies in a route-dependent manner. SC/SC immunization resulted in a significant increase in the neutralizing capacity of serum antibodies towards Efb and LukMF', shown by increased phagocytosis ofS. aureus and increased viability of bovine leukocytes. Therefore, a SC immunization route should be considered when aiming to optimize humoral immunity againstS. aureus mastitis in cattle.